-7p-(4-9p)=-10+25p/4

Simple and best practice solution for -7p-(4-9p)=-10+25p/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7p-(4-9p)=-10+25p/4 equation:


p in (-oo:+oo)

9*p-7*p-4 = (25*p)/4-10 // - (25*p)/4-10

9*p-7*p-((25*p)/4)-4+10 = 0

9*p-7*p+(-25/4)*p-4+10 = 0

6-17/4*p = 0 // - 6

-17/4*p = -6 // : -17/4

p = -6/(-17/4)

p = 24/17

p = 24/17

See similar equations:

| 5b+7+7=7+6b | | X^2=.035 | | -72XY^2+45X^2Y= | | 2,1/2x=10 | | 13-(x+7)=7x-2 | | (3a^3+a-5)-(6-5a^3-2a^2)= | | 2(4+5x)+10=(-5x+12) | | 3-27x/4=-x/2-1/4(-3x-4) | | 14x=-7+21 | | 17=4(9-2)+29 | | -3+5x=2x+6 | | -8/9-2/3 | | -4x+y=-10 | | h/9=8 | | 3x+3/2=24 | | X-4=-(3x-3)+5 | | 18A^2-24AB^3= | | 3+n-3-2n=8n-3n | | 3x-9-4x=7x+15 | | 36*-6= | | 0.5x-0.4x-2=-3 | | 2x+5+x=7-3x | | u-4/u+6 | | U=-12+-1u | | 3U=-36+-3u | | 4r+1-4r=-14+r+7+7r | | 7(x^2-9)+23=135 | | 23x-(15x-54)= | | x/3-2=x/6 | | 24+-24+3U=-12+-24+-3u | | 1/18b=-6 | | 0.3(4z+6)+43.4=0.7(4z-4) |

Equations solver categories